Effects of black soldier fly frass as a biofertilizer on growth, leaf morphology, and biomass allocation of soybean (Glycine max L. (Merr.)) under soil salinity stress - Logroño, Michael Rey M.; Cadiz, Geofe O. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Black Soldier Fly (BSF) frass is known to be a good source of fertilizer for different plant types in various countries; however, it has not been tested with nitrogen-fixing plants and its tolerance to abiotic stress. Salinity stress has been one of the main contributors to limiting crop growth and production caused by climate, poor irrigation, and improper fertilizer application. The study tested the effectiveness of BSF frass on the growth, leaf morphology, and biomass allocation of soybean (Glycine max L. (Merr.)) under salinity stress. This greenhouse experiment employed a full factorial experiment in a randomized complete block design to determine the independent and interaction effects of BSF frass and NaCl solution on soybeans. The experiment had 16 treatments from the combination of four levels of salinity (0, 0.25, 0.30, 0.35 M) and three levels of frass-soil mixture (5-95 %, 10-90 %, 15-85 %), and a control (100 % soil). Two-way ANOVA and post hoc analysis were employed to test the significant differences in the plant traits among treatment groups. Results showed that BSF frass had independent effects on all plant traits except for leaf mass fraction. NaCl solution had independent effects on root growth rate, live biomass, and leaf area. Interaction effects of these factors are evident on live biomass, leaf area, and stem and root mass fractions. Application of frass promoted optimal soybean growth at 5 % concentration. High amounts of frass (>5 %) and independent effects of NaCl solution stunted soybean?s growth and leaf morphology. Soybeans applied with frass allocate most of their biomass to the stem. In general, the addition of frass mitigated the negative effects of salinity stress but only at 5 % concentration. The results of this study provided additional agriculture protocols on the economic use of BSF frass on nitrogen-fixing plants under salinity stress.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. July 2022